Generalized unconditionally stable Crank-Nicolson PML formulations for truncating FDTD domains - Ramadan, Omar (Horizon House Publications Ltd, 2005)
An efficient and unconditional stable perfectly matched layer (PML) formulations are presented for truncating finite difference time domain grids. The formulations are based on incorporating the Crank-Nicolson scheme into the stretched coordinate PML approach. In these formulations, the field components are updated in a single step per time iteration. Numerical example carried out in one-dimensional domain shows that the formulations are both accurate and unconditionally stable.
35th European Microwave Conference (EuMC) -- OCT 04-06, 2005 -- Paris, FRANCE
Keywords: Crank-Nicolson (CN); stretched coordinate perfectly matched layer (PML); finite difference time domain (FDTD)